Wound healing across the animal kingdom: Crosstalk between the immune system and the extracellular matrix. Issue 7 (4th May 2020) - Arenas Gómez, Claudia M.; Sabin, Keith Z.; Echeverri, Karen
Abstract: Tissue regeneration is widespread in the animal kingdom. To date, key roles for different molecular and cellular programs in regeneration have been described, but the ultimate blueprint for this talent remains elusive. In animals capable of tissue regeneration, one of the most crucial stages is wound healing, whose main goal is to close the wound and prevent infection. In this stage, it is necessary to avoid scar formation to facilitate the activation of the immune system and remodeling of the extracellular matrix, key factors in promoting tissue regeneration. In this review, we will discuss the current state of knowledge regarding the role of the immune system and the interplay with the extracellular matrix to trigger a regenerative response.